Effects of learning experience on behaviour of the generalist parasitoid Sclerodermus pupariae to novel hosts. (28th December 2012) - Wei, K.; Tang, Y. L.; Wang, X. Y.; Yang, Z. Q.; Cao, L. M.; Lu, J. F.; Liu, E. S.; Liu, G. J.
Abstract Massicus raddei Blessig (Coleoptera: Cerambycidae), also referred to as the oak long‐horned beetle (OLB), is a non‐natural host for the generalist parasitoid Sclerodermus pupariae Yang et Yao (Hymenoptera: Bethylidae). To determine whether this generalist parasitoid might be a suitable agent for the control of OLB, the adaptive learning experience of adult female parasitoids to OLB larvae was investigated in the laboratory. A Y‐tube olfactometer bioassay was used to examine the effects of adaptive learning experience on the foraging ability of parasitoids for OLB larvae. The results indicated that parasitoids were significantly attracted by the volatiles of ash bark, Fraxinus velutina, with emerald ash borer (EAB), Agrilus planipennis Fairmaire (Coleoptera: Buprestidae) larvae and larval frass, after exposure to ash bark mixed with EAB larval frass (learning condition A). In contrast, after exposure to oak bark, Quercus liaotungensis, mixed with OLB larval frass (learning condition C), parasitoids showed significant preference for the volatiles of oak bark with OLB larvae and larval frass. On the basis of the results of no‐choice tests, we found that parasitoids exposed to learning condition C had greater paralysis efficiency and higher OLB larvae parasitism rates than those exposed to learning condition A or no experience. Furthermore, parasitoids fed on OLB larvae in learning condition C had significantly greater paralysis efficiency and higher OLB larvae parasitism rates than other parasitoids tested. Parasitoids fed on EAB larvae in learning condition A had the lowest paralysis efficiency and OLB larvae parasitism rates among the parasitoids tested. These findings suggested that adaptive learning significantly enhanced the ability of a generalist parasitoid to utilize a novel host. This may provide a new approach to controlling non‐natural hosts using generalist parasitoids.